Experimental Investigation of Attrition Resistance of Zeolite Catalysts in Two Particle Gas-Solid-Solid Fluidization System: Attrition Resistance of Zeolite Catalysts - Naveed, Shahid; Nawaz, Zeeshan; Xiaoping, Tang; Shu, Qing; Wei, Fei (Biological Sciences - PJSIR, 2010)
In the study of mechanical degradation of 34 ZSM-5 and SAPO catalysts, using the gas jet attrition - ASTM standard fluidized bed test (D-5757), the effect of particle size and its quantitative analysis in co-fluidization environment was investigated on the air jet index (AJI) basis. In gas-solid-solid fluidized bed reactors (GSS-FBR), two different sized particles were fluidized under isothermal conditions. In case of ZSM-5 and SAPO-34, significant attrition resistance was observed, which was attributed to small pore size and specific structural strength of the mobile framework image (MFI) and chabasite (CHA) structures, respectively. The optimum AJI for SAPO-34 and ZSM-5 (of particle size 0.2 mm) in GSS-fluidization system was observed to be 0.0118 and 0.0062, respectively. In co-fluidization, deviations from Gwyn relationship were observed due to change in impact of collision. Therefore, zeolites are recommended as suitable catalysts or catalytic supports (for doping of expensive metals) and for commercial use in GSS-FBR.